Attitudes and readiness for Global Englishes in language assessment among Indonesian university English lecturers - I Putu Andre Suhardiana; Made Wahyu Mahendra; I Gusti Ayu Indah Triana Juliari; Ida Bagus Gde Phalaguna; Astuti Wijayanti (Universitas Tidar, 2026)
The ascendance of English as the world’s dominant lingua franca is revolutionizing English Language Teaching (ELT) at every level. This acknowledges the validity of contextually suitable English variations. Even if this theoretical change is recognized, implementing it in the classroom remains a problem. This study aimed to examine how Indonesian English lecturers view Global Englishes (GE). Specifically, it aimed to measure their familiarity with GE principles, their attitudes toward modifying typical language-based assessments, and their assessed preparedness to implement such modifications. This study used a sequential explanatory mixed-methods design. The quantitative phase consisted of a census survey of 16 full-time instructors. This employs the ‘Survey of Knowledge, Attitudes, and Readiness Regarding GLOBAL ENGLISHes Principles in Language Assessment (SKAR-GE).' This was followed by a qualitative phase that included interviews with 10 lecturers to help explain the survey results. The analysis showed a mismatch between thinking and doing. Lecturers indicated a level of acquaintance with Global Englishes (GE) but showed deficiencies in objective knowledge (41.67% correct). This person mistakes English as a Lingua Franca with ‘broken English.’ They were ‘cautiously open’ to new ideas. They respected communicative pragmatics, but when GE principles went against traditional grammatical benchmarks in evaluation, they were unsure and resistant. The study finds that Indonesian English lecturers are usually open to GE ideas, but they cannot switch to GE-informed assessment because they do not grasp it well enough, hold strong native-speaker beliefs about assessment, and lack sufficient support and models.